Correlation Between Building Damage Levels and Microtremor HVSR Curve Parameters - Baiq Laelatin Diniati; Syamsuddin, Syamsuddin; Bakti Sukrisna; Kormil Saputra; Ika Umratul Asni Aminy; Rahmatun Inayah; Adella Ulyandana Jayatri; Shamim Mahabubul Haque (Frontier Advances in Applied Science and Engineering, 2024)
The level of damage caused by an earthquake is related to the physical parameters obtained from Horizontal-to-Vertical Spectral Ratio (HVSR) analysis. The dominant frequency (f0) and wave velocity are the two HVSR parameters used. This research aims to determine the type of rock and the level of damage to buildings caused by the 2018 Lombok earthquake. We used secondary data from the 2011 Mataram City microtremor, which included 85 measurement points. We conducted frequency spectrum analysis using the HVSR method and shear wave velocity (vs) inversion modeling to gain a comprehensive understanding of Mataram City seismic properties. The Poisson ratio analysis results reveal that earthquake-prone sedimentary layers dominate Mataram City. The HVSR analysis revealed a negative correlation between the damage from the 2018 earthquake and the dominant frequency and shear wave velocity. The overlay results between the dominant frequency values, shear wave velocity, and the comparison of vp and vs with the damage level from the 2018 earthquake demonstrate this.